Representation of Immigrants in British and American Newspapers - Chefneux Gabriela (Sapientia Hungarian University of Transylvania Scientia Publishing House, 2018)
One of the major functions newspapers have is that of (re)presenting reality for their readers and thus explain events and promote specific values; newspapers are multimodal texts, which resort both to language and images to convey their message. The paper analyses a British and a North American newspaper article and has two aims. Firstly, to investigate the strategies used by journalists to represent immigrants in a positive way and, secondly, to draw a comparative analysis between the articles in terms of these strategies. The theoretical part defines the concept of racism and the ways in which it is nowadays expressed and lists some of the strategies that are frequently used to present immigrants (such as topic, referential strategies, intensifying, extensivization, victimization, personalization, voices heard, argumentation, etc.) with the use of pictures. The second part identifies strategies used in these two articles. The conclusions present a comparison between them in terms of similarities (values upheld, type of argumentation) and differences (intensification and nomination strategies, quotation patterns).